Towards Deciphering the Hidden Mechanisms That Contribute to the Antigenic Activation Process of Human Vγ9Vδ2 T Cells - Boutin, Lola; Scotet, Emmanuel (Frontiers in Immunology, 2018)
Vg9Vd2 T cells represent a major unconventional gd T cell subset located in the peripheral blood of adults in humans and several non-human primates. Lymphocytes that constitute this transitional subset can sense subtle level changes of intracellular of phosphorylated intermediates of the isoprenoid biosynthesis pathway (phosphoantigens, pAgs), such as isopentenyl-pyrophosphate, during cell stress events. This unique antigenic activation process opers in a rigourous framework that requires the expression of butyrophilin 3A1 (BTN3A1/CD277) molecules, which are type I glycoproteins that belong to the B7 family. Several studies have further shown that pAgs specifically bind to the intracellular B30.2 domain of BTN3A1 which is linked to the antigenic activation of Vg9Vd2 T cells. Here, we highlight the recent advances in BTN3A1 dynamics which are induced upon the binding of pAgs and the contribution of the different subunits to this activation process. Recent reports support that conformational modifications of BTN3A1 might represent a key step in the detection of infection or tumorigenesis by Vg9Vd2 T cells. A better understanding of this mechanism will help optimize novel immunotherapeutical approaches that target defined functions of this unique gd T cells subset.